Distributed and focused attention: neuropsychological evidence for separate attentional mechanisms when counting and estimating. - Demeyere, N; Humphreys, G (2007)
Evidence is presented for 2 modes of attention operating in simultanagnosia. The authors examined visual enumeration in a patient, GK, who has severe impairments in serially scanning across a scene and is unable to count the numbers of items in visual displays. However, GK's ability to judge the relative magnitude of 2 displays was consistently above chance, even when overall luminosity did not vary with the number of items present. In addition, several variables had a differential impact on GK's counting and magnitude estimation. Magnitude estimation but not counting was facilitated by using elements that grouped more easily and by presenting the elements in regular configurations. In contrast, counting was facilitated by placing the elements in different colors while magnitude estimation was disrupted. Also GK's performance on magnitude estimation tasks was disrupted by asking him to count the elements present. The data suggest that GK can process visual stimuli in either a focused or distributed attention mode. When in a focused attention mode, performance is limited by poor serial scanning of attention due to an impaired explicit representation of visual space.